Pendampingan Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Melalui Kegiatan Latihan Dasar Kepemimpinan Organisasi Siswa Intra Madrasah (OSIM) di MTs Badridduja Probolinggo - Izzah, Ismatul; Yunita, Arifia Retna; Hayati, Nur (Journal of Smart Community Service, 2024)
Intra-school/Madrasah Student Organizations are essential to students' learning and practicing organizing and working together. The success of an organization cannot be separated from the role of a leader. Therefore, leadership is a discussion that continues to develop. Community service activities (PKM) were carried out by a team of MPI study program lecturers at Zainul Hasan Genggong Genggong Probolinggo Islamic University, and students were part of a collaboration program with the MTs Badridduja Kraksaan Probolinggo institution. This PKM aims to ensure OSIM administrators improve their organization, starting with leadership, organization, self-development, and problem-solving. Mentoring activities are integrated with implementing the Strengthening Pancasila Student Profile Project (P5) activities. In P5, there is also the formation of the character of critical reasoning, creativity, independence, faith, devotion to God Almighty, and noble character, working together and having global diversity. The results of this activity were very significant in the changes obtained; students had more integrity, Discipline, and responsibility and could communicate and collaborate well.